Chitosan oligosaccharide attenuates acute kidney injury and renal interstitial fibrosis induced by ischemia-reperfusion - Shulan Yin; Jiane Liu; Xiangzhong Zhao; Hanyu Dong; Yanjing Cao; Sudan Zhang; Xiaolei Dong; Guangmin Zhang; Shengxi Jin; Weiping Shi; Fenggang Xiang; Jizheng Gong; et al. (Renal Failure)
Acute kidney injury (AKI) and renal interstitial fibrosis are global clinical syndromes associated with high morbidity and mortality. Renal ischemia-reperfusion (I/R) injury, which commonly occurs during surgery, is one of the major causes of AKI. Nevertheless, an efficient therapeutic approach for AKI and the development of renal interstitial fibrosis is still lacking due to its elusive pathogenetic mechanism. Here, we showed that chitosan oligosaccharide (COS), a natural oligomer polysaccharide degraded from chitosan, significantly attenuates I/R-induced AKI and maintains glomerular filtration function by inhibiting oxidative stress, mitochondrial damage, and excessive endoplasmic reticulum stress both in vitro and in vivo. In addition, long-term administration of COS can also attenuate the proliferation of myofibroblasts, mitigate extra cellular matrix deposition, and thus inhibit the transition of AKI to chronic kidney disease through participating in metabolic and redox biological processes. Our findings provide novel insights into the protective role of COS against acute kidney injury.